The difference between non-profit organization financial reporting practices and financial performance in relation to IFRS for SMEs and government requirements / Jean Damascene Mvunabandi - Mvunabandi, Jean Damascene (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study explored the financial reporting practices and financial performance of non-government organizations (NGOs). A case study of a large anonymised non-profit organisation based in Durban, KwaZulu-Natal-South Africa, was conducted. A qualitative approach was employed, and data was collected through semi-structured interviews with 24 purposively selected participants to capture their thoughts. Data collected through interviews were supplemented by a review of internal confidential organisational documents. Transcripts, conventional thematic and document analysis, were used to analyse data. Empirical findings revealed that the selected organisation's financial reporting practices were not fully prepared under the International Financial Reporting Standards for small and medium enterprises (IFRS for SMEs) but differed substantially in line with different formats imposed by its external donors. Relying on empirical findings, key recommendations with a view to enabling the organisation and other similar organisations globally to meet the divergent and often conflicting with requirements of all their stakeholders without losing credibility and or compromising its principles were provided. Therefore, policymakers and other key role players should act swiftly to remedy these discrepancies. This study will guide researchers to further research on subject matter.